Protecting Our Mosts Valuable Personal Data: A Comparison Of Transborder Data Flow Laws In The European Union, United Kingdom, And Indonesia - Budi Agus Riswandi; Alif Muhammad Gultom (Universitas Islam Indonesia, 2023)
Information technology and its relationship with data protection is a crucial area that needs to be addressed, especially for data flows among different countries. In the majority of jurisdictions, international data transfers are restricted unless specific requirements stipulated by data protection laws are met. However, in the European Union (EU) and the United Kingdom (UK) there are three exceptions, adequacy, appropriate safeguards, and derogations. This paper conducts a comparative legal analysis of the regulations governing the cross-border transfer of personal data in the EU, UK, and Indonesia. The research method is normative, while the approaches employed are statutory and conceptual with an analytical and descriptive research design. The study focuses on the legal framework and the various mechanisms to protect personal data during transborder flows. The research identified both commonalities and disparities in data protection regulations in Indonesia, the EU, and the UK. Notably, differences appeared in the application of appropriate safeguards and the use of criminal sanctions in Indonesia. Finally, the study concludes by providing recommendations for future developments in the legal frameworks for cross-border data transfer in the EU, UK, and Indonesia.Keywords: Adequacy decision, Cross-border data transfer, Derogations, Personal Data Protection Law. Melindungi Data Pribadi Kita yang Paling Berharga: Perbandingan Hukum Aliran Data Lintas Batas Di Uni Eropa, Inggris, dan Indonesia AbstrakTeknologi informasi dan hubungannya dengan perlindungan data merupakan bidang penting yang perlu ditangani, terutama untuk aliran data antar negara. Di sebagian besar yurisdiksi, transfer data internasional dibatasi kecuali persyaratan khusus yang ditetapkan oleh undang-undang perlindungan data dipenuhi. Namun, di Uni Eropa (UE) dan Inggris (UK) terdapat tiga pengecualian, yaitu kecukupan, pengamanan yang sesuai, dan pengurangan. Tulisan ini melakukan analisis hukum komparatif terhadap peraturan yang mengatur transfer data pribadi lintas batas negara di UE, Inggris, dan Indonesia. Metode penelitian yang digunakan adalah normatif, sedangkan pendekatan yang digunakan bersifat perundang-undangan dan konseptual dengan desain penelitian analitis dan deskriptif. Studi ini berfokus pada kerangka hukum dan berbagai mekanisme untuk melindungi data pribadi selama arus lintas batas. Penelitian ini mengidentifikasi kesamaan dan kesenjangan dalam peraturan perlindungan data di Indonesia, UE, dan Inggris. Perbedaan yang terlihat jelas adalah penerapan safeguards yang tepat dan penggunaan sanksi pidana di Indonesia. Terakhir, studi ini menyimpulkan dengan memberikan rekomendasi untuk perkembangan masa depan dalam kerangka hukum transfer data lintas batas di UE, Inggris, dan Indonesia.Kata Kunci: Keputusan kecukupan, Transfer data lintas batas, Derogasi, Undang-Undang Perlindungan Data Pribadi.